Two new paratanaid Tanaidacea (Crustacea: Malacostraca: Peracarida) from the Hawaiian Islands, with illustrated taxonomic keys - Morales-Núñez, Andrés G.; Pelleteri, Sara; Heard, Richard W. (Zootaxa, 2016)
Two new tanaidomorphan tanaidaceans, Aparatanais hawaiensis, sp. nov. and Metatanais spinipropodus, sp. nov. represent the first members of the Family Paratanaidae to be described from the Hawaiian Islands. Aparatanais hawaiensis is distinguished from the other species of the genus by the setation of the antenna, maxilliped, chela, and pereopods. Metatanais spinipropodus is distinguished from the other three members of its genus by its chela having a strongly developed, chisel-like, spiniform seta on the inner face of propodus near the sub-distal margin of the fixed finger. The Hawaiian occurrence of M. spinipropodus extends the range for the genus Metatanais well-eastward into the mid-Pacific Ocean. This study presents the first description of a male attributable to the genus Aparatanais.